Efficacy of short term non steroidal anti-inflammatory drugs in Indian patients with axial spondyloarthritis - Shubha Bhalla; Shallu Verma; Anand Narayan Malaviya (Indian Journal of Rheumatology)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are considered the first-line drugs for axial spondyloarthritis because of their high efficacy in controlling symptoms. However, the review of the literature shows that among Caucasian patients, only ~ 1/3rd with recent disease onset and only ~10% with the long-standing disease achieved partial or complete remission. The present study was, therefore, aimed at finding out how many Indian axSpA patients achieved low-disease activity state or remission over a short period of 12 weeks. Methods: This was a retrospective study including 35 patients, both nonradiographic and radiographic axSpA, classified according to the Assessment of Spondyloarthritis International Society criteria (2009). Information was extracted from the electronic medical records for patients who had only received NSAIDs without any disease-modifying anti-rheumatic drugs or biologicals. The primary objective was to analyze the effect of continuous use of NSAIDs on their disease activity status as measured by the Ankylosing Spondylitis Disease Activity Score (ASDAS)-C-reactive protein (CRP) cutoff values at the baseline as compared to that after 3 months. Results: A total of 31/35 patients continuously treated with NSAIDs for 12 weeks showed statistically significant improvement in their disease activity status as measured by ASDAS-CRP (P < 0.05). A total of 19/35 and 12/35 patients achieved remission (i.e., ASDAS-CRP < 1.3) and low disease state (i.e., ASDAS-CRP<2.1) after 12 weeks of treatment, respectively. A total of 4/35 patients were nonresponders; they were offered biologicals. Conclusion: NSAIDs are effective in reducing ASDAS-CRP disease activity status. The efficacy of NSAIDs observed in this study was much higher than that reported in European/North American patients. The reason for this difference needs further study.